Stromule formation is dependent upon plastid size, plastid differentiation status and the density of plastids within the cell - Waters, Mark; Fray, Rupert; Pyke, Kevin (Blacwell Publishing, 2004)
Stromules are motile extensions of the plastid envelope membrane, whose roles are not fully understood. They are present on all plastid types but are more common and extensive on non-green plastids that are sparsely distributed within the cell. During tomato fruit ripening, chloroplasts in the mesocarp tissue differentiate into chromoplasts and undergo major shifts in morphology. In order to understand what factors regulate stromule formation, we analysed stromule biogenesis in tobacco hypocotyls and in two distinct plastid populations in tomato mesocarp. We show that increases in stromule length and frequency are correlated with chromoplast differentiation, but only in one plastid population where the plastids are larger and less numerous. We used tobacco hypocotyls to confirm that stromule length increases as plastids become further apart, suggesting that stromules optimise the plastid-cytoplasm contact area. Furthermore, we demonstrate that ectopic chloroplast components decrease stromule formation on tomato fruit chromoplasts, whereas preventing chloroplast development leads to increased numbers of stromules. Inhibition of fruit ripening has a dramatic impact on plastid and stromule morphology, underlining that plastid differentiation status, and not cell type, is a significant factor in determining the extent of plastid stromules. By modifying the plastid surface area, we propose that stromules enhance the specific metabolic activities of plastids.